The Role of the Media in the Process of Shaping the Skills and Attitudes of Lower Secondary School Students - Michalak-Dawidziuk, Joanna (Kultura-Społeczeństwo-Edukacja, 2019)
Media play an important role in social and personal life. They affect opinion forming, promote trends and shape skills and attitudes. Their impact is enormous. Media can have both positive and negative influence, as they are addressed to adults and young people, whose opinions and characters have not yet crystallised. Thus the question about the extent to which the media shape abilities pertaining to the recognition of individual educational needs and learning, which is “(…) the foundation for success at school, in continuing education and in professional life.” Results of research conducted among lower secondary school students provide answers to these questions.